CONCEPT OF RETRACTABLE CONSENT IN MINISTER OF EDUCATION’S REGULATION REGARDING SEXUAL VIOLENCE ON CAMPUS - Adi Lazuardi; Muhammad Akbar Pribadi (STIH Putri Maharaja, 2022)
The Regulation of Minister of Education, Culture, Research and Technology (Permendikbud) 30/2021 is a response to the high level of sexual violence case perpetrated by individuals in universities in Indonesia. The existence of a victim's consent instrument in Permendikbud 30/2021 as a differentiator between sexual violence and a consensual relationship is a new thing in legal regulation in Indonesia. This research aims to explain the concept of retractable consent and its application in Permendikbud 30/2021. This study uses a descriptive analysis method to data sources on regulations that are considered relevant to the agreement of the parties in general, and regulations related to sexual violence in particular. The results show that retractable consent in cases of sexual violence is the consent of one of the parties involved in sexual activities that can be withdrawn or canceled at any time, even when sexual activity has started. In this concept, the agreement has the nature of sustainability. Permendikbud 30/2021 regulates the invalidity of consent with certain conditions, so that the consent given by one of the parties in a sexual activity can be considered legally invalid. According to Permendikbud 30/2021 victims of sexual violence who apply personal consent retraction (cancellation or withdrawal of consent for personal reasons) should also be included in the victim category.